Permission Management Method for before and after Applications the Update in Android-based IoT Platform Environment - Park, In Kyu; Kwak, Jin (2018 International Conference on Platform Technology and Service, PlatCon 2018, 2018)
The Android-based IoT(Internet of Things) platform just like the existing Android provides an environment that makes it easy to utilize Google's infrastructure services including development tools and APIs through which it helps to control the sensors of IoT devices. Applications running on the Android-based IoT platform are often UI free and are used without the user's consent to registered permissions. It is difficult to respond to the misuse of permissions as well as to check them when they are registered indiscriminately while updating applications. This paper analyzes the versions of before and after an application the update running on the Android-based IoT platform and the collected permission lists. It aims to identify the same permissions before and after the update, and deleted and newly added permissions after the update were identified, and thereby respond to security threats that can arise from the permissions that is not needed for IoT devices to perform certain functions.
Keywords: Android IoT platform; Android permissions; Android securities; Android update; Development tools; Infrastructure services; Management method; Security threats; Android IoT platform; Android permissions; Android security; Android update